2019
DOI: 10.1111/cch.12732
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between parental incarceration and children's emotional and behavioural development: Results from a population cohort study

Abstract: Background: Parental incarceration (PI) is associated with adverse developmental outcomes for children affected. However, research in this area often reports conflicting results with few studies following children across time in non-U.S.populations. Additionally, more research is called for using multi-informant perspectives rather than relying on adult reports of child outcomes alone.Methods: This study used data from the first two waves of a nationally representative cohort study of 8,568 children aged 9 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…In this respect, the results of our research correspond with the results of studies conducted by other authors, who reported that, although numerous mediating factors were controlled for, the risk of negative consequences in psychosocial development was still increased among prisoners’ children [ 4 , 5 , 6 ]. Our results are consistent with those reported by other authors both as regards the higher level of externalizing problems in prisoners’ children [ 2 , 14 , 15 , 16 ] and as regards the higher level of internalizing problems [ 14 , 15 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this respect, the results of our research correspond with the results of studies conducted by other authors, who reported that, although numerous mediating factors were controlled for, the risk of negative consequences in psychosocial development was still increased among prisoners’ children [ 4 , 5 , 6 ]. Our results are consistent with those reported by other authors both as regards the higher level of externalizing problems in prisoners’ children [ 2 , 14 , 15 , 16 ] and as regards the higher level of internalizing problems [ 14 , 15 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, Kinner and colleagues [ 14 ] found a higher level of externalizing behavior in boys. Several studies also confirmed that parental incarceration was related to children’s internalizing problems–depression [ 14 , 15 ], anxiety [ 14 , 17 ]–and to social stigma [ 18 ].…”
Section: Introductionmentioning
confidence: 93%
“…Importantly, children affected by PI are at increased risk of experiencing multiple social and economic stressors (Bradshaw et al, 2020). Gender differences in children's social and emotional development are well-established (e.g., Farrington et al, 2012); besides this, household socioeconomic status (SES), stressful life events (SLEs) (Kjellstrand et al, 2020), PCG age, and PCG level of education (Pogarsky et al, 2006) can all have negative consequences for children's emotional and behavioral development.…”
Section: The Present Studymentioning
confidence: 99%
“…Ferraro and Shippee (2009) discuss how this accumulated stress compounds in later life and can increase the aging process, resulting in poor health outcomes, and these stressful life events have been demonstrated even in children as young as nine in a study by Bradshaw et al. (2020). In this study, which looked at the impact of parental incarceration, children of these parents were found to report more anxiety and report more life stressors.…”
Section: Introductionmentioning
confidence: 99%